Unions, change and crisis : French and Italian union strategy and the political economy, 1945-1980 /: French and Italian union strategy and the political economy, 1945-1980. (2016) - Lange, Peter, 1944-; Ross, George, 1940-; Vannicelli, Maurizio
No abstract available